Rare pancreas tumor mimicking adenocarcinoma: Extramedullary plasmacytoma - Akyuz, Filiz (Baishideng Publishing Group Co., Limited, 2014)
Neoplastic proliferation of plasma cells is called plasma cell dyscrasias, and these neoplasms can present as a solitary neoplasm or multiple myeloma. Extramedullary plasmacytoma, in particular pancreatic plasmacytoma, is a rare manifestation of multiple myeloma. Although computerized tomography is useful for the diagnosis of extramedullary plasmacytoma, there are no specific radiologic markers that distinguish it from adenocarcinoma. Histological confirmation by biopsy is necessary for accurate diagnosis and management of the tumor. Endosonography is the most sensitive method for the diagnosis of pancreatic tumors, and the use of fine needle aspiration by endosonography is associated with a lower risk for malignant seeding and complications. Here, we report a case of pancreatic plasmacytoma in newly identified multiple myeloma as diagnosed by endosonography. Endosonography is a reliable and rapid method for the diagnosis of extramedullary plasmacytoma. Therefore, endosonographic fine needle aspiration should be the first choice for histological evaluation when pancreatic plasmacytoma is suspected. Ideally, the pathology would be performed at the same site as endosonographic biopsy.